Stop Thinking and Start Doing: Three-Year Accelerator-to-Practice Program as a Market-Based Solution for Legal Education - Jeffrey J. Pokorak; Ilene Seidman; Gerald M. Slater (Washington University Journal of Law & Policy, 2014)
Law school applications are the lowest they‘ve been in thirty years. Law school enrollment is down significantly from last year, and analysts see the trend continuing for the 2014–2015 academic year. The lack of current job opportunities and the potential for massive student loan payments has scared away prospective students from entering the legal profession. Commentators continue to suggest that obtaining a legal education might no longer be worth the investment. This Essay disagrees. Too many people suffer unnecessary harms due to a lack of affordable legal services. Continued progress in achieving necessary access to legal assistance relies on a constant influx of new, talented, and energetic lawyers. Providing the best training possible to each new generation of lawyers is essential for the continued development of individual liberties and the equitable treatment of all in our society. Many thinkers throughout legal academia are responding to these concerns by carefully considering what steps will actually help students, institutions, and the overall system of justice. Too many respond to current concerns about legal education with what we believe is the primary fallacy of legal educators today: namely, that the mission of law schools is to prepare students to think like lawyers. This Essay argues that the central function of law school is to prepare students to be lawyers, and to do what lawyers do. Although these two aims might seem similar, they are actually representative of the wide gulf between two distinct concepts: that of law school as a liberal arts education in law and that of law school as a professional education for lawyers. These goals are not mutually exclusive, but the former concept has dominated legal study development. Decisions regarding curriculum, faculty appointments, standards for promotion and tenure, and pay incentives have solidified legal academia‘s preference for the theoretical over the experiential approach to learning.
Keywords: legal education reform; market solution for legal education; clinical education